AN ISLAMIC LEGAL PERSPECTIVE ON CONTEMPORARY HEALTH ISSUES: INTEGRATING TRADITIONAL AND MODERN APPROACHES - Ali Abdulghani, Naser; Husayn Alrumayh, Safa (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
This article explores the intersection of Islamic law and modern health practices, analyzing how traditional Islamic principles address contemporary health issues such as mental health, medical ethics, and the use of modern medicine. Islam has long had a profound influence on the healthcare practices of its followers, with guidelines rooted in the Qur'an and Hadith (sayings of the Prophet Muhammad). However, with the rapid development of modern medical technologies and global health challenges, there has been a growing need to reconsider Islamic legal principles in relation to modern health needs. This study presents an in-depth analysis of how Islamic jurisprudence can contribute to health policy in the modern world, focusing on issues like bioethics, reproductive health, and patient rights. Through a critical examination of primary Islamic texts and contemporary scholarly interpretations, the article provides a framework for reconciling Islamic legal doctrines with emerging health challenges. The findings indicate that while Islamic teachings can offer significant guidance in medical decision-making, there remains a need for continuous reinterpretation of Islamic jurisprudence to address the complexities of modern healthcare.